Characterization of a novel canine T-cell line established from a dog with cutaneous T-cell lymphoma. Issue 2 (November 2017) - Hara, Kyohei; Iio, Aki; Asahina, Ryota; Takahashi, Maiko; Mori, Takashi; Nishida, Hidetaka; Kamishina, Hiroaki; Sakai, Hiroki; Kitoh, Katsuya; Mizuno, Takuya; Tsujimoto, Hajime; Maeda, Sadatoshi
Highlights: Canine cutaneous T-cell lymphoma (CTCL) has the potential to be used as a model animal for human primary cutaneous aggressive epidermotropic CD8 + cytotoxic T-cell lymphoma (CD8 + PCECTL). A novel canine CTCL cell line, termed EO-1, was established from a dog with CTCL. EO-1 expressed CD3 and CD8 with a high expression of a functional CC chemokine receptor 4 that was biologically active to both human and mouse CCL17/TARC. EO-1 may be a useful tool in the research for not only canine CTCL but also human CD8 + PCECTL.